1998
DOI: 10.1159/000006786
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antioxidant Vitamins C and E on Atherosclerosis in Lipid-Fed Rabbits

Abstract: Background: Antioxidant vitamins are hypothesized to help prevent atherosclerosis by blocking lipoprotein oxidation. We investigated the effects of dietary vitamins C and E on atherosclerosis in rabbits. Methods and Results: Forty New Zealand male rabbits were divided into 4 groups: 0.3% cholesterol diet with (LV) and without vitamin (LC), and 0.5% cholesterol diet with (HV) and without vitamins (HC). The treated groups consumed 137 ± 8 mg/day vitamin C and 80 ± 4 mg/day vitamin E for 10 weeks. Vitamin treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…In support of our findings, a double-masked placebo-controlled randomized clinical trial has shown that long-term supplementation of nondepleted men with a reasonable dose of vitamin E alone or in combination with slow release vitamin C reduces lipid peroxidation [20]. However, in previous reports by Kinlay et al [21] and by Sun et al [22], they did not demonstrate a significant protective effect on lipids in human and animal. Thus, it is plausible that the effects of TFA and the combination of vitamin E plus C on lipid metabolism might be involved in other mechanisms in addition to the antioxidant.…”
Section: Discussionsupporting
confidence: 83%
“…In support of our findings, a double-masked placebo-controlled randomized clinical trial has shown that long-term supplementation of nondepleted men with a reasonable dose of vitamin E alone or in combination with slow release vitamin C reduces lipid peroxidation [20]. However, in previous reports by Kinlay et al [21] and by Sun et al [22], they did not demonstrate a significant protective effect on lipids in human and animal. Thus, it is plausible that the effects of TFA and the combination of vitamin E plus C on lipid metabolism might be involved in other mechanisms in addition to the antioxidant.…”
Section: Discussionsupporting
confidence: 83%
“…The results have been conflicting, ranging from increased fatty streaks in vitamin C-deficient guinea pigs 15 to no effects of vitamin C supplementation in cholesterol-fed rabbits. 16 LDL oxidation in Apoe Ϫ/Ϫ mice occurs in vivo as demonstrated by increased amounts of circulating autoantibody against oxidized LDL, 17 and antioxidants, such as vitamin E and N,N-diphenyl 1,4-phenylenediamine, have been shown to reduce atherosclerosis in Apoe Ϫ/Ϫ mice. 18,19 In support of a role for vitamin E, Apoe Ϫ/Ϫ mice that also lack vitamin E transfer protein and have vitamin E deficiency (Ͻ10% normal in plasma) had modest but significant increases in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of total cholesterol in male mongrel rabbits fed a high fat diet was also markedly suppressed by vitamin E, which was attributed to the higher levels of 7␣-hydroxylase, an enzyme involved in the conversion of cholesterol to bile acids. 19 On the other hand, supplementation with vitamin E did not reduce hypercholesterolemia in New Zealand rabbits 28,29 and hamsters. 30 One explanation put forth by Shen et al 30 for the inconsistent effect of vitamin E on plasma cholesterol, at least in hamsters, is that the effect of vitamin E is only manifested under conditions of high cholesterol feeding, which sets the stage for vitamin E-induced alterations in the generation of cholesteryl ester transfer protein activity from adipose tissue.…”
Section: Discussionmentioning
confidence: 94%
“…While there are studies that have shown a hypocholesterolemic effect of vitamin E, [18][19][20][21][22] certain studies have shown no effect of vitamin E on serum lipids. [28][29][30] For example, findings by Phonpanichrasamee et al 18 show that oral supplementation with 2,100 IU vitamin E/week lowered cholesterol by 50% after 8 weeks of supplementation. Elevation of total cholesterol in male mongrel rabbits fed a high fat diet was also markedly suppressed by vitamin E, which was attributed to the higher levels of 7␣-hydroxylase, an enzyme involved in the conversion of cholesterol to bile acids.…”
Section: Discussionmentioning
confidence: 99%